Advertising and Markups: The Case of the German Brewing Industry - Simon Pröll; Klaus Salhofer; Giannis Karagiannis (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2019)
The beer market in Germany may be described as a monopolistic competition with many breweries supplying a very large variety of different beer styles and brands. Advertising is one means of differentiating a product and increasing prices over marginal costs. Based on production data obtained from a sample of 197 German breweries and thirteen years of observation, we derive firm-specific markups, profit ratios and prices in each year and relate those to their advertising expenditures and firm size. We are able to show that advertising expenditures are positively correlated to a brewery's markup, profit ratio and price while firm size is negatively correlated.
Keywords: D22; L11; L66; 330; advertising; markup; imperfect competition; brewing